Development Of Tourism Villages With The Application Of Simple Accounting To Business Actors In Pematang Serai Village, Langkat District - Nur Aliah; Miftha Rizkina (Proceeding of The International Conference on Business and Economics, 2023)
This study aims to determine the application of simple accounting carried out by the Pematangs erai tourism village community who have a business. This research approach with qualitative descriptive method. The sample of this research is a business actor in the village of Pematang Serai which is as many as 8 business actors. The data analysis technique used is direct observation using interviews and documentation. The results of this study are Pematang serai is a village in langkat district that has potential in the development of village tourism, the development of this tourist village is supported by the langkat government, people who have a business in the village have not applied simple accounting records.